Management of Plasmodium vivax risk and illness in travelers - Baird, J. Kevin (Trop Dis Travel Med Vaccines, 2017)
Malaria poses an exceptionally complex problem for providers of travel medicine services. Perceived high risk of exposure during travel typically prompts prescribing protective antimalarial drugs. Suppressive chemoprophylactic agents have dominated strategy for that practice for over 70 years. This broad class of therapeutic agents kills parasites after they emerge from the liver and attempt development in red blood cells. The dominance of suppressive chemoprophylaxis in travel medicine stems largely from the view of Plasmodium falciparum as the utmost threat to the patient – these drugs are poorly suited to preventing Plasmodium vivax and Plasmodium ovale due to inactivity against the latent liver stages of these species not produced by P. falciparum. Those hypnozoites awaken to cause multiple clinical attacks called relapses in the months following infection. Causal prophylactic agents kill parasites as they attempt development in hepatic cells. The only drug proven effective for causal prophylaxis against P. vivax is primaquine. That drug is not widely recommended for primary prophylaxis for travelers despite preventing both primary attacks of all the plasmodia and relapses of P. vivax. The long-held perception of P. vivax as causing a benign malaria in part explains the dominance of suppressive chemoprophylaxis strategies poorly suited to its prevention. Recent evidence from both travelers and patients hospitalized in endemic areas reveals P. vivax as a pernicious clinical threat capable of progression to severe disease syndromes associated with fatal outcomes. Effective prevention of clinical attacks of vivax malaria following exposure during travel requires primary causal prophylaxis or post-travel presumptive anti-relapse therapy following suppressive prophylaxis.